ANALYSIS OF THE IMPACT OF DIGITAL MARKETING ON SALES OF MANCO "CIMUT" IN TAMBAKMAS MADIUN VILLAGE - Titik Hartiningsih; Intan Puspitasari; Basuki Rahmat (International Journal of Economics, Science, and Education, 2024)
This research aims to apply digital marketing strategies to Manco Cimut MSMEs and determine their impact in increasing their sales. Digital marketing is a combination of marketing strategies using internet-based information technology. This can be implemented using social media or e-commerce platforms which are much in demand by society today. Many business actors market their products based on the internet on the grounds that implementing digital marketing can facilitate marketing and increase product sales. This research is field research with the research object being Manco Cimut as one of the home industries that produces manco in Tambakmas village. The sources used are primary and secondary data, namely interviews, observations and literature reviews to strengthen theory. The research results show that Manco Cimut uses digital marketing as its marketing and promotional media. The marketing strategy used utilizes social media applications such as Instagram and WhatsApp. Social media is used to inform product variants, availability of goods, ordering and purchasing facilities as well as communicating with consumers. This platform is quite effective for use as marketing and sales advice because many people use social media, so product information is more easily spread even outside the region. However, obstacles still arise that Manco Cimut faces in implementing digital marketing, including unstable internet connections, delays in delivery, and human resources in managing online marketing and sales development. The impact of implementing digital marketing carried out by Manco Cimut is quite significant in increasing sales of Manco Cimut products, as evidenced by the large number of orders from inside and outside the city.